Mathematics for civil engineers : an introduction - Yang, Xin-She (Dunedin Academic Press, 2018)
Civil Engineers use mathematics as part of their daily routine. In this introductory book Dr Yang provides methods for practical application as well as an introductory text for undergraduate students.
Keywords: Civil engineering -- Mathematics.; Engineering mathematics.; elektronické knihy; electronic books